Tolerable level of corruption for foreign direct investment in Africa - Anselm Komla Abotsi; Tongyai Iyavarakul (Contemporary Economics, 2015)
Corruption has become endemic in many African countries and is difficult to eradicate completely; therefore, reducing corruption to a tolerable level that will not deter foreign investors must be the aspiration of all political leaders and stakeholders. This study tries to identify the level of corruption that is tolerable to foreign investors, which is referred to as the Tolerable Level of Corruption for Investment (TLCI). The study proposes that below the TLCI, corruption plays the role of "sand in the wheels of commerce" and thus has a negative impact on FDI inflows, but above the TLCI, corruption functions to "grease the wheels" and has a positive impact on FDI inflows. The study is based on secondary data collected from the World Bank World Development Indicators. Using a dynamic panel data estimation technique while controlling for other variables, the estimated TLCI in Africa is -0.27 on the control of corruption scale, which ranges from approximately -2.5 (weak) to 2.5 (strong). Therefore, all African leaders and stakeholders, especially in countries that fall below the TLCI, should intensify their efforts in the fight against corruption to reduce corruption in their respective countries to at least the TLCI to attract foreign investors.
Keywords: F18; F23; F20; F30; 330; corruption; tolerable level of corruption for investment; foreign direct investment; institutions